Influence of ligands within Al-based metal-organic frameworks for selective separation of methane from unconventional natural gas. (April 2023) - Yu, Yixuan; Shang, Mingyang; Kong, Lingtong; Li, Xianhai; Wang, Lina; Sun, Tianjun
Abstract: Efficient CH4 /N2 separation from unconventional natural gas is vital for both energy recycling and climate change control. Figuring out the reason for the disparity between ligands in the framework and CH4 is the crucial problem for developing adsorbents in PSA progress. In this study, a series of eco-friendly Al-based MOFs, including Al-CDC, Al-BDC, CAU-10, and MIL-160, were synthesized to investigate the influence of ligands on CH4 separation through experimental and theoretical analyses. The hydrothermal stability and water affinity of synthetic MOFs were explored through experimental characterization. The active adsorption sites and adsorption mechanisms were investigated via quantum calculation. The results manifested that the interactions between CH4 and MOFs materials were affected by the synergetic effects of pore structure and ligand polarities, and the disparities of ligands within MOFs determined the separation efficiency of CH4 . Especially, the CH4 separation performance of Al-CDC with high sorbent selection (68.56), moderate isosteric adsorption heat for CH4 (26.3 kJ/mol), and low water affinity (0.1 g/g at 40% RH) was superior to most porous adsorbents, which was attributed to its nanosheet structure, proper polarity, reduced local steric hindrance, and extra functional groups. The analysis of active adsorption sites indicated that hydrophilic carboxyl groups and hydrophobic aromatic ring were the dominant CH4 adsorption sites for liner ligands and bent ligands, respectively. The methylene groups with saturated C–H bonds enhanced the wdV interaction between ligands and CH4, resulting in the highest binding energy of CH4 for Al-CDC. The results provided valuable guidance for the design and optimization of high-performance adsorbents for CH4 separation from unconventional natural gas. Graphical abstract: Image 1 Highlights: Experimental and DFT data were combined to explore interactions for CH4 separation. Synergetic effects of pore structure and ligand polarity determined CH4 separation. Al-CDC possessed high SSP and moderate Q s t − C H 4, preceding most porous adsorbents. CH4 preferred carboxyl groups for liner ligand and aromatic rings for bent ligand.